Seep's Shrot Story Number: Research and Critical Analysis - Kosar Perveen; Dr. Shagufta Hussain (بازیافت, 2021)
Literary journals serve as a reflection of the intellectual and creative trends of their time. Magazines and journals are the greatest source of enlightenment from new literary movements and new perspectives. Quarterly Magazine Seep (Karachi) has been instrumental in promoting the tradition of Urdu fiction. In addition to publishing special editions of Urdu fiction, it enriched the tradition of Urdu fiction by publishing and representing the works of important and renowned fiction writers of the subcontinent.